ENDOBRONCHIAL ULTRASOUND-GUIDED TRANS-BRONCHIAL NEEDLE ASPIRATION FOR THE DIAGNOSIS OF GRANULOMATOUS VERSUS NON GRANULOMATOUS LUNG DISEASES: Endobronchial Ultrasound-Guided Trans-Bronchial Needle Aspiration - Ambreen, Shumaila; Naseem, Arshad; Ahmed, Jamal; Khan, Aiza Saadat; Shah, Syed Wasib; Raja, Sohail Khan; Khan, Aslam; Ansari, Jawad Khaliq (Pakistan Armed Forces Medical Journal, 2018)
Objective: To evaluate the diagnostic accuracy of Endo-bronchial ultrasound guided transbronchial needle Aspirationin patients with mediastinal lymphadenopathy and mass lesions especially in the context of granulomatousversus non granulomatous lung disorders.Study Design: Open label, unblended prospective observational cohort.Place and Duration of Study: Department of Pulmonology, Pak Emirates Military Hospital Rawalpindi, from Jul2015 to Mar 2016.Patients and Methods: All patients presented during study periods with meditational lymphadenopathy orlesions in which the initial bronchoscopy did not reveal any diagnosis were included in the study. Endobronchialultrasound-guided transbronchial needle aspiration was performed in the bronchoscopy suit under conscioussedation and local anesthesia. Rapid on site evaluation was available for most of the cases. The procedure wasperformed using an integrated fibreoptic bronchoscopy with 22G TBNA needle by an experienced Bronchoscopist.The data was analyzed by using SPSS version 21Results: A total of 53 patients with mean age of 44 years underwent endobronchial ultrasound-guided transbronchialneedle aspiration for evaluation of meditational or hilar lesions between Jul 2015 to Apr 2016. There were43 (81.1%) male and 10 (18.8%) female patients. A total of 108 Lymph nodes were sampled in 53 patients, rapid onsite evaluation was available in 41 (77.3%) patients. Adequate representative sample could be obtained in 45 of 53(84.9%) patients. The overall diagnosis were chronic granulomatous lesion in 27 (50.9%) patients, squamous cellcarcinoma in 10 (18.8%), lymphoproliferative disorder in 2 (3.7%), thymoma in 1 (1.3%) and reactive hyperplasiain 5 (9.4%) of cases. No major complication of the procedure was observed.Conclusion: End bronchial ultrasound-guided transbronchial needle aspiration was found useful diagnosticmodality for lymph nodes sampling in patients with lymphadenopathy and mass like lesions in mediastinum.